THE ACCOUNTING EXCHANGE. - Gregory, Homer E.; Burrell, O.K.; Stillman, A.B.; Littleton, A.C. (The Accounting Review, 1930)
Abstract Many credit men and bankers tend to place a high value upon the condition of the current ratio as found in balance sheets in extending credit to borrowing clients. In many instances the ratio of current assets to current liabilities is taken for granted without adequate reasons being given for the underlying causes that brought about the change from a former position. In a particular balance sheet, the ratio may show the same figure of, three to one at the close of each of two fiscal periods, or it may show a change to a decidedly higher ratio of four to one, or again to a lower ratio of two to one. The credit man should analyze his balance sheet far enough to ascertain whether or not the improvement in the working capital was caused by the investment of inside money or outside money. Bonds involved mortgage liability and increased overhead costs. Capital stock naturally has no foreclosure possibility, but demands its rent. The changes in the ratio, caused by increases or decreases in the working capital are fundamental. They are apt to be permanent, therefore, should be analyzed carefully, in order to ascertain if the financial structure has been altered seriously by the change, as for example the flotation of bonds to fund the current debts.